Detection of Antibiotic Residues from Shrimp Pond and Their Environment in East Java Province Indonesia - Suprapto, Hari; Sulmartiwi, L.; Sudarno, Sudarno (Aquacultura Indonesiana, 2015)
Indonesia shrimp products are often rejected by foreign countries due to high antibiotic content, whereas a few years ago Japan and European countries are set 0.05 ppb permitted to consume by the people, but now the restriction will be smaller is 0.01 ppb. Some farmer was stopped to use antibiotics but the residues still found in fish flesh. Possible origins antibiotics are environment because are antibiotic residues still exist in the mud, water organism which lived in pond. Samples originating from shrimp, mud, water and other biota will be examined according to the method of Thomson (1966) of the Pfizer Corporation and the Association of Official Analytical Chemist (Horwitz, 1980). The purpose of this study was to determine the origin of antibiotic present in the cultivation or farming system that does not use antibiotics in shrimp production.: a. Antibiotics obtained from ponds in the Tuban area is 1.8 ppm (mud), 0.8 ppm (water) and 2.1 (biota). b. a. Antibiotics obtained from ponds in Gresik were 0.6 ppm (mud), 0.3 ppm (water) and 1.2 (biota). c. Antibiotics obtained from ponds in the area of Situbondo are 0.3 ppm (mud), 0.1 ppm (water) and 0.6 (biota). d. a. Antibiotics obtained from ponds in the area are 0.3 ppm Probolinggo (mud), 0.2 ppm (water) and 0.6 ppm (biota).